PELATIHAN DAN PENGEMBANGAN MODEL DESAIN KEMASAN MODERN KELURAHAN SENDANGGUWO - Scorina Dwiantari; Irene Nathalia Setiawan; Bambang Heriawan (Gapenas Publisher, 2024)
Packaging is a tool to increase the selling value of products and marketing strategies from producers to consumers. Understanding the importance of packaging design that is useful to attract more buyers and expand the marketing network to MSME actors. However, there are still many MSME actors who do not know the benefits of using packaging with modern designs, so there are still many MSME actors who sell their products using cracker bags for consumers to bring as souvenirs or souvenirs, because they do not understand the importance of using packaging with a more modern and innovative design. The results of this activity are able to apply the knowledge gained to make their own model designs and designs according to the size and needs of the product so that they can compete in a wider marketing network and acquire the ability to innovate product packaging design